ACCURATE PRONUNCIATION FOR EFFICIENT COMMUNICATION - Rauber, Andréia Schurt; Koerich, Rosana Denise (Revista Expectativa, 2000)
An efficient executive secretary needs to devote special attention to communication skills, and intelligible pronunciation is essential for communicating effectively. While in the office or on the phone, this professional is constantly exposed to situations in which a word incorrectly used or pronounced may result in embarrassing situations or even damage an important business transaction. In this article, we will discuss about some frequently mispronounced English sounds by Brazilian English as a foreign language speakers that could be avoided if some attention be given to these pronunciation aspects. The sounds to be dealt with in this article are (1) the consonants in word-final position, (2) the /s/ clusters, (3) the final /l/, (4) the nasals, and (5) the unstressed h words.